ANALISIS KEBIJAKAN PEMASARAN (7P) SEPEDA MOTOR YAMAHA PADA DEALER UTAMA JAYA MOTOR SIANTAN - Muhammad Zalviwan; Petronela (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2021)
This study aims to determine the marketing policy (7P) of Yamaha motorbikes at the Jaya Motor Siantan Main dealer. The research method that I use in this research is survey research which takes a sample of a population using a questionnaire as the main data collection tool. The population in this study were all consumers and communities around the main dealer Jaya motor Siantan, North Pontianak, the sample was taken as many as 100 respondents using the incidental sampling technique. The results of research on the marketing policies carried out by the Utama Jaya Motor Siantan dealership show that: the product aspect with an average of 4.24 is in the very good category. The price aspect is in the good category with an average of 4.06. The place aspect (location) with an average of 3.66 in the category is quite good. The aspect of promotion (promotion) with an average of 3.97 in the good category. Aspects of the people (people) with an average of 4.00 in the good category. The process aspect with an average of 4.10 in the good category and the physical evidence aspect with an average of 3.24 in the very bad category.